A breakage and adhesion regime map for the normal impact of loose agglomerates with a spherical target. Issue 12 (16th July 2015) - Nguyen, Duy; Rasmuson, Anders; Thalberg, Kyrre; Niklasson Björn, Ingela
Abstract : Discrete element method‐based analysis is conducted to investigate the effects of interface energy between particles on the breakage and adhesion of loose agglomerates upon impact with a spherical target. A mechanistic approach is tested to find a relationship between particle properties, kinetic energy, and the agglomerate structure after the impact, which resulted in a new dimensionless number, the ratio of the two interface energies. In combination with Δ, a dimensionless number relating incident kinetic energy to agglomerate strength (Moreno‐Atanasio and Ghadiri M, Chem Eng Sci . 2006;61(8):2476–2481), a good description of the agglomerate impact is obtained. The agglomerate structure after impact is mapped using the two dimensionless numbers and is in good agreement with experimental observations. The constructed regime map can serve as a guide for selecting preliminary process parameters in adhesive particle mixing. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4059–4068, 2015